Pengurangan Isolasi Sosial pada Klien “DI” Pengidap Penyakit Skizofrenia Paranoid melalui Intervensi Social Skill Training - Ananda Lufi Nabila; Mari Esterilita (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
Abstract: The prevalence of schizophrenia sufferers in Indonesia is in the range of 0.3% to 1% of the population, one of which is paranoid schizophrenia, which is the most common type with the main symptoms of delusions and hallucinations. Social isolation is one of the most common behaviors, covering around 72% of people with schizophrenia. This study aims to reduce the level of social isolation in clients "DI", sufferers of paranoid schizophrenia who carry out social isolation through Social Skill Training interventions. The method used is case work with the stages of Engagement, Intake, and Contract, Assessment, Planning, Intervention, Evaluation and Termination. The results show positive changes in clients, namely: 1) clients have dared to leave the house 2) Clients have started working with working hours of 4-6 hours per day 3) clients have interacted a lot with family and new people. In conclusion, this Social Skill Training Intervention can be an effective model to be applied to other clients with similar conditions